Deliberative Politics through Citizens’ Participatory Democracy: A model for Africa Political Processes - Andrew Osehi Enaifoghe (Journal of Social and Development Sciences, 2019)
This article explores the present crisis of democratic governance or administration in Africa and examines the elective capability of deliberative majority rules system of democracy, in which the desire of the general public is educated by mindful, engaged citizen’s commitment and conversation. There are various questions needing answers; are the various and spellbound citizenry even equipped for consultation? How likely is amass thought of deliberation to achieve a very much contemplated choice? Wouldn’t it gather consultation reproduce a similar power lopsided characteristics blocking different sorts of talk? Deliberative models are displayed in principle and practical discourse, with contextual investigations including the furious populism of the Brexit vote, the ascent of deliberative components. What the contributing creators do share is the acknowledgement that the authenticity of appointive portrayal or representatives endures when individuals in the majority rule system of governments end up frustrated, disillusioned, and repelled. This study gives challenging and convincing thoughts regarding how to re-establish confidence in popular democratic governments by making them stronger and responsive. This study adopted a qualitative method of analysis.